Understanding cybercrime and digital deviance - Graham, Roderick (Cybercrime and digital deviance, 2024)
This chapter lays out the basic terms and philosophy underlying the textbook and the authors associated with it. Specifically, ideas fundamental to understanding the concepts of cybercrime and digital deviance are presented and discussed. The reader is further offered the five basic challenges a person studying cybercrime may encounter, illustrated using the case of former state representative Nick Sauer and accusations of revenge porn. Additionally, as the two authors represent fundamentally different disciplines converging to create the textbook, they present the reader with a second edition of the original publication that expands upon an interdisciplinary approach to the stated material with broader reference to international content and a concerted effort to reduce US-centric biases.